Letter from Mary-Louise MacDonagh to her daughter Mary MacDonagh, Sister Francesca - MacDonagh, Mary-Louise; MacDonagh, Mary Josephine, 1872-1954 (1907)
Mary-Louise MacDonagh informs Mary that Joe, her brother, is doing well and only needs to be examined by a doctor.
Handwritten annotation on first page "John's mother".
Keywords: MacDonagh, Joseph, -- 1883-1922; MacDonagh, Mary Josephine -- Correspondence; MacDonagh, Mary-Louise -- Correspondence; Ireland -- History -- 1901-1910